Role of Information Technology in work: Life Balance - Pranjal, Shreyasi (International Journal of Management, Innovation & Entrepreneurial Research, 2015)
Work-life balance refl ects an individual’s orientation across career roles and non-carrier life roles as an incompatible inter-role phenomenon. In the transition to an information-based global economy, the lines between work and home are blurring as technology reshapes the work place and the nature of home life evolves. Information technology (IT) has become a vital and integral part of every individual’s life. From a teenager who loves technologically advanced cum latest gadgets and an adult who is addicted of using cloud-computing technology as for data’s storing. The reasons for the omnipresent use of computer technology in the real world can best be determined by looking at how it is being used across the real world. Role of IT in balancing work-life is all about delivering ease, effi ciency and maintaining individual’s healthy environment. There are numerous roles of IT which makes us integrally prominent, smart and active, and makes an effective aura in between work-life. Role of IT in work-life balance has been an electrifying current investigation subject from the recent years; the purpose of the research role of IT in work-life balance shows the how IT makes individuals life convenient, promising, stressless, and relatively safe.